Turkish psychometric characteristics of the humanistic practice ability of nursing scale: differences by education, working year, and professional satisfaction - Ayse Sahin; Bedia Tarsuslu; Aslı Yilmaz; Filiz Kuni; Gulgun Durat (BMC, 2024)
Abstract Background Humanistic nursing practices scientifically improve the knowledge structure of nursing, enrich its theoretical system and support its development. Therefore, it is crucial to evaluate the humanistic practice abilities of nurses. Objective This study aimed to test the psycholinguistic features, language and construct validity of the Humanistic Practice Ability of Nursing Scale and to examine it according to nurses' demographic characteristics. Design and methods This study was a methodological type of analytical research conducted with 397 clinical nurses working in a hospital. A questionnaire including demographic information and evaluating empathy and compassion adequacy was used. Data were analyzed using explanatory and confirmatory factor analysis, Cronbach's alpha, item-total score correlation, split-half analysis, t-test, analysis of variance and correlation analysis. Results The scale consists of 29 items and four factors, explaining 61.15% of the total variance. Factor loads were > 0.30. confirmatory factor analysis results were χ2/df: 2.58, GFI: 0.86, TLI: 0.91, IFI: 0.92, CFI: 0.92, RMSEA: 0.06, and SRMR: 0.03. The Cronbach alpha value for the full scale is 0.95. A significant relationship was found between the scale and empathy and compassion proficiency. It was observed that the scale scores differed according to the nurses' education level, working years and job satisfaction (p < 0.05). Conclusion This study shows that the Turkish version of the HPAN scale is valid and reliable for 29 items and four factors. The humanistic practice ability of nurses differ according to postgraduate education, years of working in the profession and professional satisfaction.